The eastward enlargement of the eurozone: social and policy aspects in Portugal, Spain and Italy - Aurora Galego; José Caétano; Sofia Costa; Reilika Liiv (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This report explores some features of the social dimension of enlargement regarding the Southern EU-Member countries, namely Portugal, Spain and Italy. Economic theory suggests that integration may affect wages, employment and income distribution through changes on trade, FDI and migration flows. By removing all barriers to the free movement of goods and services, capital and labour, Eastward Enlargement will affect the location of economic activities, innovation, and technology. Subsequently, the need for economic readjustments will impose extra difficulties at national, regional and sector levels. These aspects have been analysed in several studies, stressing that the regional and social dimension of enlargement as well as the effects on cohesion, have to be taken into account when conceiving EU policies.
Keywords: G1; E2; 330; enlargement; labour markets; southern EU-members; EMU